Analisis Rancang Bangun Implementasi SCADA System Untuk Peningkatan Performa Mesin Produksi Pada Proses Washing Component Manufacture Engine Assembling: Indonesia - Bimas Putra Hariyanto (Energi & Kelistrikan, 2023)
This paper presents how to increase the effectiveness of automobile manufacturing in terms of production machine performance. Automobile companies are one of the many industries that exist in various countries. This is because automobiles are transportation products that are widely used both for the purpose of transporting people and goods. Poor production machine performance will disrupt internal productivity to the point that it will affect the stability of industrial profits. One of the factors causing poor engine performance is due to predictive maintenance analysis activities that are still not optimal. SCADA system development will focus on monitoring equipment before it becomes abnormal (predictive maintenance) in real time. The monitoring and control method is carried out automatically by using sensors for data retrieval and a programmable logic controller as a remote terminal unit. Then, data will be sent to the server via CC-Link IE Field Communication and later be recorded and analyzed through the SCADA display. The results of research optimizing engine performance using the SCADA system are effective, with an increase in engine performance of 96.2% for downtime and 97.0% for frequency trouble.